Analisis Keterampilan Mengelola Kelas Pada Pembelajaran Micro Mahasiswa PGSD Semester VI - Catur Annisa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2021)
This study aims to determine the ability of classroom management teaching skills possessed by PGSD students in the 6th semester of class B for the academic year 2020/2021 in micro learning courses. To achieve the research objectives, the researchers used three stages, namely the planning, implementation and evaluation stages. This study uses quantitative research methods with an ex post facto approach. The first stage carried out is the planning stage, in the planning stage students make a Learning Implementation Plan (RPP) according to the predetermined class and theme that will be used in micro learning. The second stage is the implementation stage, at this stage students teach using lesson plans which have been used as a reference in practicing teaching in micro classes. The last stage is evaluation, at this stage when students are carrying out teaching activities, other students provide an assessment using the Class Management Skills Questionnaire. Based on the results of this study, the average value of class management skills possessed by PGSD 6th semester Class B students for the 2020/2021 academic year in micro learning courses is 0.57%. So, it can be concluded that the class management skills possessed by 6th semester PGSD students in class B are included in the good category.